SEKOLAH DIINDONESIA - Widodo, Slamet (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT Many school bUildings are affected by destructive earthquake in Indonesia. This paper presents the current conceptions. re evant to seismic : sk for construction in urban centre that depends on seismiC hazard, vulnerability and bUilding value. School building as an important education facility is being analyzed here, the analysis including social economics value, school buildings structures in Indonesia, construction norms and damage to school buildings in the past. Keywords: Earthquake, school bUildings